Visuospatial cognition in acute unilateral peripheral vestibulopathy - Oh, Sun-Young; Nguyen, Thanh Tin; Kang, Jin-Ju; Kirsch, Valerie; Boegle, Rainer; Kim, Ji-Soo; Dieterich, Marianne (Frontiers in Neurology, 2023)
Background This study aims to investigate the presence of spatial cognitive impairments in patients with acute unilateral peripheral vestibulopathy (vestibular neuritis, AUPV) during both the acute phase and the recovery phase. Methods A total of 72 AUPV patients (37 with right-sided AUPV and 35 with left-sided AUPV; aged 34–80 years, median 60.5; 39 males, 54.2%) and 35 healthy controls (HCs; aged 43–75 years, median 59; 20 males, 57.1%) participated in the study. Patients underwent comprehensive neurotological assessments, including video-oculography, video head impulse and caloric tests, ocular and cervical vestibular-evoked myogenic potentials, and pure-tone audiometry. Additionally, the Visual Object and Space Perception (VOSP) battery was used to evaluate visuospatial perception, while the Block design test and Corsi block-tapping test assessed visuospatial memory within the first 2 days (acute phase) and 4 weeks after symptom onset (recovery phase). Results Although AUPV patients were able to successfully perform visuospatial perception tasks within normal parameters, they demonstrated statistically worse performance on the visuospatial memory tests compared to HCs during the acute phase. When comparing right versus left AUPV groups, significant decreased scores in visuospatial perception and memory were observed in the right AUPV group relative to the left AUPV group. In the recovery phase, patients showed substantial improvements even in these previously diminished visuospatial cognitive performances. Conclusion AUPV patients showed different spatial cognition responses, like spatial memory, depending on the affected ear, improving with vestibular compensation over time. We advocate both objective and subjective visuospatial assessments and the development of tests to detect potential cognitive deficits after unilateral vestibular impairments.